2009
DOI: 10.1080/03008200902846270
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Cyclic Stretching on Distribution and Gene Expression of Integrin and Cytoskeleton by Ligament Fibroblasts In Vitro

Abstract: Cyclic stretching is pivotal to maintenance of the ligaments. However, it is still not clear when ligament fibroblasts switch on expression of genes related to the mechanotransduction pathway in response to cyclic stretching. This in vitro study investigated, using ligament fibroblasts, the time-dependent changes in distribution and gene expression of β1 integrin, the cytoskeleton, and collagens after the application of 6% cyclic stretching at a frequency of 0.1 Hz for 3 hr on silicon membranes. We carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…The mechanosensitivity of FA assembly and downstream signaling is well documented, and thus they are prime candidates for mediating cellular responses to stretch (26). Indeed, the cytoskeletal reorientation that occurs in response to cyclic stretch requires several proteins that localize to FA, including integrins (27), zyxin (28), paxillin (25), Src, and p130 Crk-associated substrate (p130Cas) (29), and involves sliding reorganization of FAs (6). However, the effects of sustained stretch on FA organization and dynamics have not been explored.…”
mentioning
confidence: 99%
“…The mechanosensitivity of FA assembly and downstream signaling is well documented, and thus they are prime candidates for mediating cellular responses to stretch (26). Indeed, the cytoskeletal reorientation that occurs in response to cyclic stretch requires several proteins that localize to FA, including integrins (27), zyxin (28), paxillin (25), Src, and p130 Crk-associated substrate (p130Cas) (29), and involves sliding reorganization of FAs (6). However, the effects of sustained stretch on FA organization and dynamics have not been explored.…”
mentioning
confidence: 99%
“…Cyclic stretching is an example of biomechanical stimuli that increase collagen synthesis by cells in the tissue, thereby strengthening the resultant scaffold made of aligned fibre bundles (Goulet et al, 2000, Kaneko et al, 2009). Thus, the ACL substitute has already reached a first step towards matrix synthesis, and the process can continue to progress in response to the in vivo strains that are applied to the graft in the post-transplantation environment (Goulet et al, 2004).…”
Section: Role Of Biomechanical Stimulation In Generating An Effectivementioning
confidence: 99%
“…With regard to the latter, recent studies have shown that 10 min to 3 hr of cyclic uniaxial loading with tensile strains of 2.5-15% and frequencies of 0.1-1 Hz induce the collagens I and III expression by fibroblasts and mesenchymal stem cells (MSCs) on twodimensional surfaces [22,23], in three-dimensional constructs [9][10][11], and on braided or woven constructs [21]. In addition, Teh et al-using electrospun fibers on woven mesh supports-showed that cyclic mechanical stretch and fiber orientation act synergistically to stimulate expression of the connective tissue ECM genes collagen I and III, and tenascin-C by MSCs [24].…”
Section: Introductionmentioning
confidence: 99%